OPTIMIZATION OF ANTENNA DEPLOYMENT FOR TWO-DIMENSIONAL RFID LOCALIZATION - Savochkin, D. A.; Gimpilevich, Yu. B. (Radio Electronics, Computer Science, Control, 2015)
This paper presents a method of search for the optimal antenna deployment for use in spatial localization systems based on the radio frequency identification technology (RFID). It involves minimizing the average error of a combinational localization method consisted of a trilateration algorithm, fingerprinting algorithm, and an intersectional algorithm. During the computational experiment we found the optimal solution among several antenna deployment patterns for a square localization field. The solution is a grid pattern with antenna interrogation zones oriented towards the field center.